Desentralisasi dalam Kerangka Demokratisasi dan Good Governance - Yunus, Yasril (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
Actually, decentralization is autonomization of a society. It is not only an end but also as an instrument of services distribution and development to increase social prosperity. In the case of â€œgood governanceâ€ distribution of public services need to involve private sector and other communities with the implementation of principles of transperancy, accountability, efficiency, justice, and law enforcement. Kata Kunci: desentralisasi, demokratisasi, otonomi daerah, good governance